Utilizing Heart Rate Variability for Coaching Athletes During and After Viral Infection: A Case Report in an Elite Endurance Athlete - Hottenrott, L.; Gronwald, T.; Hottenrott, K.; Wiewelhove, T.; Ferrauti, A. (Frontiers in Sports and Active Living, 2021)
Background: Viral diseases have different individual progressions and can lead to considerable risks/long-term consequences. Therefore, it is not suitable to give general recommendations on a time off from training for athletes. This case report aims to investigate the relevance of detecting heart rate (HR) and HR variability (HRV) during an orthostatic test (OT) to monitor the progression and recovery process during and after a viral disease in an elite endurance athlete.